PENGARUH FAKTOR PENGELOLAAN SUMBER DAYA MANUSIA (SDM) TERHADAP KUALITAS LAYANAN REHABILITASI DI KLINIK BNNP JAWA TIMUR - Titik Trisnowati; Henry Sudiyanto; Arief Fardiansyah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Rehabilitation service quality is an important consideration for drug addicts in accessing rehabilitation services. Effective human resources management is necessary to improve the personal performance of staff, which impacts healthcare service quality. The objective of this research is to understand the influence of human resources management on the quality of rehabilitation services at the East Java BNNP Clinic. This study used a cross-sectional method with total sampling of 108 clients. Data collection was conducted using Google Forms completed by respondents and analyzed using Path Analysis with a significance level (?) of 0.05. Competence has an influence on officer performance by 0.395. Discipline has an influence on officer performance by 0.249. Cooperation has an influence on officer performance by 0.230. Competence has an influence on rehabilitation service quality by 0.219. Discipline has an influence on rehabilitation service quality by 0.217. Cooperation has an influence on rehabilitation service quality by 0.165. Officer performance has an influence on rehabilitation service quality by 0.331. There is a significant influence of competence on rehabilitation service quality through officer performance by 0.130. There is no significant influence of discipline on rehabilitation service quality through officer performance. There is a significant influence of cooperation on rehabilitation service quality through officer performance by 0.076. To improve the quality of rehabilitation services, it is recommended to enhance competence, discipline, cooperation, and officer performance.